The Intellectual Crisis of the Ummah: Revisiting the Past Patterns of Thought - al-Ghazali, Muhammad (Islamic Studies, 2022)
These notes are a slightly revised version of a keynote address delivered by the author at a two-day international conference on the “Intellectual Crises of the Muslim Ummah: Rethinking Traditional Solutions,” held at the Aligarh Muslim University, India, on April 6-7, 2015.